ANALYTICAL DETERMINATION OF Co3+ CATION WITH GOSSIPOL-2-AMINO-4-METHYLPYRIDINE (Scientific journal of the Fergana State University, 2023)
This article presents various conditions for the analytical determination of the Co3+ ion of the Schiff base (di(2-amino, 4-methylpyridine)) obtained on the basis of the substance gossypol isolated from cotton, which is considered a local raw material.